SMART CAMPUS ONLINE LECTURE MODEL AS AN ALTERNATIVE EDUCATION EQUITY STRATEGY IN THE ERA OF SUPER SMART SOCIETY 5.0 - Adnan, Adnan; Aiyub, Aiyub; Roziq, Adya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study aims to analyze the effect of the Smart Campus Online Lecture Model on Education Equity in the Super Smart Society 5.0 Era in Aceh Province. The sample in the study was 150 (one hundred and fifty) students and lecturers as respondents. The sampling technique used non-probability sampling technique. The data obtained from the distribution of questionnaires to the respondents were processed by the SPSS program. Methods of data analysis using quantitative analysis methods. The results of the study partially show that the online lecture model has a significant effect on Education Equity with a significant value = 0.005, the Smart Campus variable has a significant effect on Education Equity with a significant value = 0.003. And the results of this study indicate that the smart campus online lecture model has an effect on educational equity by 72.9 percent. Based on the results of the study, it shows that the online lecture variable has a very good role for equal distribution of education because it can reach various areas that have not been served or have not had the opportunity to be able to experience higher quality education in 3 T areas and the smart campus model variable is appropriate. many campuses must apply it more optimally in implementing the smart campus model so that later it can provide maximum service to all users of educational services.